2018
DOI: 10.1631/jzus.b1800155
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D2 polymorphism is associated with alleviation of obesity after 8-year follow-up: a retrospective cohort study in obese Chinese children and adolescents

Abstract: Objective: The aim of this study was to explore the association of dopamine receptor D2 (DRD2) polymorphism and alleviation of obesity in children and adolescents after 8-year follow-up. Methods: This retrospective cohort study included obese children and adolescents with a follow-up period of 8 years. Baseline clinical characteristics and DRD2 polymorphisms (including rs1076562, rs2075654, and rs4586205) were extracted from medical records. A follow-up visit was performed in May 2017 to collect related data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous study has reported the regulatory role of DRD2 gene in metabolism through mediating food intake behavior. In a study on childhood obesity, the rs2075654 polymorphism of DRD2 gene was determined to be associated with long-term obesity alleviation in obese Chinese children and adolescents [Zhu et al, 2018]. Besides, Cardel et al have also reported the close relationship between the Taq1a polymorphism (rs1800497) of DRD2 gene with diet and adiposity in a multi-ethnic cohort of children [Cardel et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported the regulatory role of DRD2 gene in metabolism through mediating food intake behavior. In a study on childhood obesity, the rs2075654 polymorphism of DRD2 gene was determined to be associated with long-term obesity alleviation in obese Chinese children and adolescents [Zhu et al, 2018]. Besides, Cardel et al have also reported the close relationship between the Taq1a polymorphism (rs1800497) of DRD2 gene with diet and adiposity in a multi-ethnic cohort of children [Cardel et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, it may seem contradictory that individuals with a genetic susceptibility to addictive eating and obesity would have such a positive response to bariatric surgery. However, compliance to addiction treatment has been observed in alcoholics with the A1 polymorphism [103]. Bromocriptine treatment (dopamine agonist therapy) proved to produce the most significant attenuations in craving and anxiety amongst A1 carrier alcoholics [103].…”
Section: Discussionmentioning
confidence: 99%
“…However, compliance to addiction treatment has been observed in alcoholics with the A1 polymorphism [103]. Bromocriptine treatment (dopamine agonist therapy) proved to produce the most significant attenuations in craving and anxiety amongst A1 carrier alcoholics [103]. This genotype was associated with reductions in body weight, fat mass, and BMI after among subjects who underwent resistance training and calorie restriction for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 A retrospective cohort study in Chinese children and adolescents with obesity also found that DRD2 rs2075654 is related to long-term remission of obesity. 47 Similarly, the polymorphism of the brain-derived neurotrophic factor (BDNF) Val66Met is associated with Conscientiousness and obesity in adolescents. 48,49…”
Section: Confoundingmentioning
confidence: 99%